Воин Пустоши: [фантастический роман] / Андрей Левицкий - Левицкий Андрей Юрьевич (Технотьма, 2010)
Экземпляры: аб. (20240226) / Инвентарный номер: 64494 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Л 37 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445